Pengaruh Struktur Modal, Profitabilitas, dan Pertumbuhan Penjualan terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Kontrol pada Sektor Consumer Non-Cylicals yang Terdaftar di Bursa Efek Indonesia Periode 2018-2023 - Shiti Maysaroh; Gatot Nazir Ahmad; Andy Andy (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of capital structure, profitability, and sales growth on firm value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. A quantitative research method was employed. The sample consisted of 62 companies selected through purposive sampling, based on the criterion of consistently publishing annual financial reports throughout the study period. The data analysis technique used was panel data regression with the aid of EViews software. The results indicate that capital structure, as measured by the Debt to Equity Ratio (DER), has a positive effect on firm value. Profitability, measured by Return on Equity (ROE), has a negative effect on firm value. Sales growth has no significant effect on firm value. Additionally, firm size as a control variable does not affect firm value.